Die Historischen quellen der Identität Mitteleuropas - Brzechczyn, Krzysztof (Logos, 2003)
The aim of this paper is analyse the notion of Central Europe used in historiography. The author reconstructs different meanings of this term used in the works of George Schopflin, Peter Burke, Oskar Halecki, Piotr Wandycz. This notion has not only geographic but also social and historical meaning.
Keywords: Mitteleuropa